2018
DOI: 10.1111/joca.12190
|View full text |Cite
|
Sign up to set email alerts
|

Debt Literacy and Debt Literacy Self‐Assessment: The Case of Poland

Abstract: It is well documented that financial literacy is at best moderate around the world and that the cost of ignorance in this field may be high on both microeconomic and macroeconomic levels. We surveyed a representative sample of Poles to measure their debt literacy—a little‐studied aspect of financial literacy—and therefore obtain insight into the factors predicting it. Our study evidenced low levels of debt literacy and its overestimation by respondents in their self‐reports. We also confirmed some of the patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 54 publications
3
25
0
5
Order By: Relevance
“…Secondly, perhaps those parents who were identified as active in teaching our respondents were unable to teach them successfully because of the low level of their own financial literacy. Such a view is supported by numerous studies pointing out significant shortcomings in financial literacy among adult Poles, especially in the oldest cohorts that can be matched to parents of our respondents (see, e.g., [84]).…”
Section: The Effect Of Parental Financial Socialisation On Young Adulsupporting
confidence: 69%
See 1 more Smart Citation
“…Secondly, perhaps those parents who were identified as active in teaching our respondents were unable to teach them successfully because of the low level of their own financial literacy. Such a view is supported by numerous studies pointing out significant shortcomings in financial literacy among adult Poles, especially in the oldest cohorts that can be matched to parents of our respondents (see, e.g., [84]).…”
Section: The Effect Of Parental Financial Socialisation On Young Adulsupporting
confidence: 69%
“…Respondents' self-assessments of their debt-related knowledge (i.e., confidence) were measured with a 5-point Likert scale. This variable came from a survey item, used in many previous studies (e.g., [4,69,83,84]), that asked: 'On a scale of 1 to 5, where 1 means very low and 5 means very high, how would you assess your debt knowledge?' This question preceded the objective diagnosis of debt literacy.…”
Section: Financial Learning Outcomesmentioning
confidence: 99%
“…Moreover, from a cognitive perspective highly literate consumers may be more likely to have the Socratic 'I know that I know nothing' reflection: the ignorant is unaware of their shortcomings and, as a result, will not strive to eliminate the deficiency. Finally, many previous studies have found strong positive links between financial literacy and income (or wealth) (Cwynar et al, 2018;Hung, Parker, & Yoong, 2009;Klapper, Lusardi, & van Oudheusden, 2015;Lusardi & Tufano, 2015), suggesting that more literate individuals may have stronger incentives to look for financial adviceas predicted by the theory of Jappelli and Padula (2013)or may be more able to pay for advice (Collins, 2012).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 86%
“…Specifically, debt advice-seeking behaviour may be the subject to what individuals believe they know about credits, loans and debt management or, in other wordsto their debt-related confidence. Research indicates significant deviations of such confidence from actual debt literacy on the part of considerably many consumers (Cwynar, Cwynar, & Wais, 2018;Porto & Xiao, 2016;Xia, Wang, & Li, 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Debt literacy has been measured in Poland previously, including the channels through which consumers acquire the literacy. Cwynar et al (2018) surveyed a representative sample of adult Poles (N = 1,004) with a twelve-question 'true/false' test probing their debt literacy on a scale from −12 to 12. The mean test score in the total sample reached −1.22, meaning that the average grown-up Pole is actually debt-illiterate.…”
Section: Introductionmentioning
confidence: 99%